A kinetic design approach to multistage aerated lagoons - Hum, Ke-siong Eddie; Nguyen, Cong Thanh; Orth, H. M.; Chongrak Polprasert; Vongvisessomjai, S.; The King's (Royal Thai Government) Scholarship (Bangkok : Asian Institute of Technology, 1983)
Multistage lagoons operated at dual-power level have many advantages over a single system. Mathematical formulations which have been proposed for the design of multistage aerated lagoons are empirical in nature and are the representation of the overall performance of the system with no conside- ration of the internal interactions which lead to the overall system beha- viour. In this study, a kinetic design approach which is based on established mechanisms of substrate removal and growth was developed to represent the steady state responses in multistage aerated lagoons. Data obtained from the laboratory are presented to verify the validity of the proposed formulations. The formulae presented here require the determination of nine parameter values. The Newton-Raphson method coupled with sensitivity analysis was used to optimize the values of the parameters. The dynamic nature of the batch process with well defined initial conditions provided the data for the identification of the parameters. The proposed formulations were also com- pared with the well-known Monod model including endogeneous respiration constant, kd. It was found that the proposed formulae gave a better des- cription of substrate removal and growth. The proposed model was able to explain quantitatively the three phases of growth of acclimated micro- organisms.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Technical Science
Thesis (Ph.D.) - Asian Institute of Technology
Keywords: Carbon monoxide -- Environmental aspects